Pengaruh Buku Suplemen Digital Terintegrasi Mitigasi Bencana Berbantuan LKPD terhadap Keterampilan Kolaborasi Peserta Didik Materi Sistem Ekskresi di SMPN 32 Padang - Arifa Chairiyah; Muhyiatul Fadilah (ISLAMIKA, 2023)
Skills training is one of the skills required to be developed in 21st century competencies. Skills training is a very important social skill for students to have, especially in learning science. Science learning requires students to understand scientifically so that students get direct experience. The purpose of this study was to determine the effect of using disaster integrated digital supplement books on students' skills in excretion system material at SMPN 32 Padang. The research method used is quasi-experimental. The instruments used in this study were questionnaires and observation sheets. The data analysis technique of this research is adjusted to the qualitative data analysis flow. Based on the results of the research, it means that the use of digital supplement books is integrated with the impact of disasters on students' skills on excretion system material at SMPN 32 Padang. In both classes there are also significant differences in scores between the experimental class and the control class. Based on the average of the two classes, the experimental class that was treated had a higher average of 72 compared to the average of the control class, which was 65.